2016
DOI: 10.1001/jamapediatrics.2015.4365
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Deprivation With Reduction in Insulin Sensitivity as Assessed by the Hyperglycemic Clamp Technique in Adolescents

Abstract: ; for the Brazilian Metabolic Syndrome Study (BRAMS) Investigators IMPORTANCE The association between short sleep duration and decreased insulin sensitivity in adolescents has been described. However, to our knowledge, no studies have investigated this association measuring insulin sensitivity by the hyperglycemic clamp technique. OBJECTIVES To compare the distributions of parameters of insulin resistance in adolescents with sleep deprivation vs adequate sleep, and to investigate the association between sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Moreover, Koren et al 31 found that a sleep duration between 7 and 8.5 h per night in obese children and adolescents was associated with optimal glucose homeostasis. Although these two studies 30, 31 have reported a U-shaped relationship between sleep duration and T2D biomarkers, similar to the relationship seen in adults, 11, 12, 13 other studies 19, 25, 26, 27, 28, 29, 32, 33, 34, 35 in the pediatric population did not or could not report the linearity or the shape of the relationship between sleep duration and glucose homeostasis biomarkers.…”
Section: Inadequate Sleep As a Contributor To Type 2 Diabetes In Chilmentioning
confidence: 65%
See 3 more Smart Citations
“…Moreover, Koren et al 31 found that a sleep duration between 7 and 8.5 h per night in obese children and adolescents was associated with optimal glucose homeostasis. Although these two studies 30, 31 have reported a U-shaped relationship between sleep duration and T2D biomarkers, similar to the relationship seen in adults, 11, 12, 13 other studies 19, 25, 26, 27, 28, 29, 32, 33, 34, 35 in the pediatric population did not or could not report the linearity or the shape of the relationship between sleep duration and glucose homeostasis biomarkers.…”
Section: Inadequate Sleep As a Contributor To Type 2 Diabetes In Chilmentioning
confidence: 65%
“…These findings are not surprising when considering that most studies, regardless of the methods or the study design used, have reported no association between sleep duration and blood glucose levels in children. 16, 17, 20, 22, 23, 24, 25, 28, 29, 30, 32, 36, 37 Nevertheless, one study by Zhu et al 35 did find a negative association between glucose and sleep time after adjusting for adiposity, maturation, age, sex and obstructive sleep apnea. Overall, these studies indicate that glucose may not be the prime marker in the association between short sleep duration and T2D in the pediatric population.…”
Section: Inadequate Sleep As a Contributor To Type 2 Diabetes In Chilmentioning
confidence: 98%
See 2 more Smart Citations
“…Attention was paid to minimize such sources of variability. Conversely, it is possible that without an overnight stay, which could disrupt sleep and worsen metabolic outcomes [9,10], there may have been less metabolic stress. This may have helped counter any increase in variability arising from other sources as an outpatient.…”
Section: Discussionmentioning
confidence: 99%